PERANAN STRATEGI PEMBELAJARAN BERDASARKAN TINGKAT PERKEMBANGAN KOGNITIF DALAM PEMBELAJARAN FISIKA PADA SEKOLAH MENENGAH PERTAMA DI KOTA MAKASSAR - Muh Agus Martawijaya (Universitas Negeri Makassar, 2012)
Abstract:The Role of Learning Strategy Based on the Cognitive Development Stage toward Physics Learning in Junior High School at Makassar. This research uses experimental desing combined ex post facto survey type, generally it intends to get a description of how far the learning strategy based on the level of cognitive development (SPBTPK) designed to the context of Phisics learning development level in Makassar. In particular, this study aims are to determine: (1) the achievement percentage of junior high school students’ cognitive development level in Makassar in accordence with their year (class), (2) the presence or absence og significant difference between learners who followed the learning based on level og cognitive development with learners who followed conventional learning in logic operations capabilities, (3) the presence or absence or significant difference between learners who followed the learning based on level of significant development with learners who followed conventional learning in Physics learning outcomes; anda (4) understanding about cognitive development level for Physics educators of junior high school in Makassar. The research result explained that: (1) the level of students’ cognitive development in all junior high school where research was conducted to whow that they have not reached the level of achievement 60% of the hilghest score that possible to be reached from Cognitive Development Level test given, (2) the average score of cognitive development level test result reached by learners of the experimental group was higher than learners of the control group, although differences is still insignificant, (3) the average score of Physics learning outcome achieved by learners of th experimental group was higher than the learners of control group learners, although differences is still insignificant, and (4) Pyhsics control group learning educators’ understanding about cognitif development in state junior high school of Makassar has not reached the achievement level 60% of the highest score yet which possible to be gotten from Cognitive Development Understanding test given.Abstrak:Peranan Strategi Pembelajaran Berdasarkan Tingkat Perkembangan Kognitif dalam Pembelajaran Fisika pada Sekolah Menengah Pertama di Kota Makassar. Penelitian ini menggunakan disain eksperimen digabung expost facto jenis yang secara umum bertujuan untuk memperoleh gambaran mengenai seberapa jauh strategi pembelajaran berdasarkan tingkat perkembangan kognitif (SPBTPK) yang dirancang dalam konteks pembelajaran Fisika dapat mempercepat keterlambatan pencapaian tingkat perkembangan kognitif peserta didik SMP di kota Makassar. Secara khusus penelitian ini bertujuan untuk mengetahui: (1) persentase pencapaian tingkat perkembangan kognitif peserta didik SMP di kota Makassar sesuai dengan usianya; (2) ada tidaknya perbedaan nyata antara peserta didik yang mengikuti pembelajaran berdasarkan tingkat kemampuan operasi logik; (3) ada tidaknya perbedaan nyata antara peserta didik yang mengikuti pembelajaran berdasarkan tingkat perkembangan kognitif dengan mereka yang mengikuti pembelajaran biasa dalam hal hasil belajar Fisika; dan (4) pemahaman tentang tingkat perkembangan kognitif bagi pendidik mata pelajaran Fisika SMP di kota Makassar. Hasil penelitian menunjukkan bahwa: (1) tingkat perkembangan kognitif peserta didik pada semua SMP yang menjadi lokasi penelitian memperlihatkan bahwa mereka belum mencapai tingkat pencapaian 60% dari skor tertinggi yang mungkin dicapai dari tes Tingkat Perkembangan Kognitif yang diberikan; (2) skor rata-rata hasil tes tingkat perkembangan kognitif yang dicapai oleh peserta didik kelompok eksperimen lebih tinggi daripada peserta didik kelompok kontrol, meskipun perbedaan tersebut masih ada yang tidak signifikan; (3) skor rata-rata tes hasil belajar Fisika yang dicapai oleh peserta didik kelompok eksperimen lebih tinggi daripada peserta didik kelompok kontrol, meskipun perbedaan tersebut masih ada yang tidak signifikan dan (4) pemahaman para peserta didik mata pelajaran Fisika SMP Negeri Makassar belum mencapai tingkat pencapaian 60% dari skor tertinggi yang mungkin dicapai dari tes Pemahaman Perkembangan Kognitif yang diberikan.Kata Kunci: SPBTPK, tingkat perkembangan kognitif, hasil belajar Fisika, pemahaman tentang tingkat perkembangan kognitif.